Chrysanthemum bizarre, a new species of Chrysanthemum from Hunan, China - Meng, Shi-Yong; Wu, Lei; Shen, Chu-Ze (Phytotaxa, 2020)
Chrysanthemum bizarre (Asteraceae), a new species from Hunan Province, China, is described and illustrated. It is similar to Chrysanthemum vestitum in that its leaves are pubescent, and the ray florets are white. However, it differs from C. vestitum in that the abaxial pubescence of C. bizarre (6.5%) is much more sparsely appressed than that of C. vestitum (64.9%). The leaf blade is triangular ovate with its base extending downward on both sides of petiole to form wings. Only one capitulum, of which the outmost phyllaries are leaflike, develops at the tip of every flowering scape rather than forming an unconsolidated cyme synflorescence. In addition, the lectotype of C. vestitum was designated in this study.